Generation and characterization of a zebrafish gain-of-function ACOX1 Mitchell disease model - Raas, Quentin; Wood, Austin; Stevenson, Tamara J.; Swartwood, Shanna; Liu, Suzanne; Kannan, Rangaramanujam M.; Kannan, Sujatha; Bonkowsky, Joshua L. (Frontiers in Pediatrics, 2024)
Mitchell syndrome is a rare, neurodegenerative disease caused by ACOX1 gain-offunction mutation (c.710A>G; p.N237S); fewer than 20 patients have been reported. Affected patients have leukodystrophy, seizures, and hearing loss. ACOX1 is the rate-limiting enzyme in peroxisomal beta-oxidation of very long chain fatty acids (VLCFAs). The N237S substitution has been shown to stabilize the active ACOX1 dimer, resulting in dysregulated enzymatic activity, increased oxidative stress, and glial damage. Mitchell syndrome lacks a vertebrate model, limiting insights into the pathophysiology of ACOX1-driven white matter damage and neuroinflammatory insults.We report a patient presenting with rapidly progressive white matter damage and neurological decline, who was eventually determined to have an ACOX1 N237S mutation using whole genome sequencing. We developed a zebrafish model of Mitchell syndrome, using transient ubiquitous overexpression of the human ACOX1 N237S variant tagged with GFP. We assayed zebrafish behavior, oligodendrocyte numbers, expression of white matter and inflammatory transcripts, and analysis of peroxisome counts.The patient experienced progressive leukodystrophy and died 2 years after presentation. The transgenic zebrafish show a decreased swimming ability that was rescued with the reactive microglia targeted anti-oxidant dendrimer-N-acetyl-cysteine conjugate (D-NAC). The mutants had no effect on oligodendrocyte counts, but did display activation of the integrated stress response (ISR). Using a novel SKL-targeted mCherry reporter, we found that mutants had reduced density of peroxisomes.We developed a vertebrate (zebrafish) model of Mitchell syndrome, using transient ubiquitous overexpression of the human ACOX1 N237S variant. The transgenic mutants have motor impairment and evidence of activated ISR, but interestingly no changes in oligodendrocyte counts. However, the mutants had a deficiency in the number of peroxisomes, suggesting a possible shared mechanism with the Zellweger spectrum disorders.